1999
DOI: 10.1038/sj.cgt.7700015
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical development of human granulocyte-macrophage colony-stimulating factor-transfected melanoma cell vaccine using established canine cell lines and normal dogs

Abstract: Tumor vaccines and gene therapy have received significant attention as means of increasing cellular and humoral immune responses to cancer. We conducted a pilot study of seven research dogs to determine whether intradermal injection of canine tumor cells transfected via the Accell particle-mediated gene transfer device with the cDNA for human granulocyte-macrophage colony-stimulating factor (hGM-CSF) would generate biologically relevant levels of protein and result in demonstrable histological changes at sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…In canine cells, it has been shown that a radiation dose between 15 and 100 Gy is sufficient to block completely the cloning capacity of the tumor cells. 23 We confirmed that a single dose of 30 Gy on D17 and Abrams cell lines inhibited cell proliferation (data not shown). Consequently, canine cell lines were inactivated with a single dose of 30 Gy after infection and viral replication was assessed.…”
Section: Neutralization Assayssupporting
confidence: 69%
See 1 more Smart Citation
“…In canine cells, it has been shown that a radiation dose between 15 and 100 Gy is sufficient to block completely the cloning capacity of the tumor cells. 23 We confirmed that a single dose of 30 Gy on D17 and Abrams cell lines inhibited cell proliferation (data not shown). Consequently, canine cell lines were inactivated with a single dose of 30 Gy after infection and viral replication was assessed.…”
Section: Neutralization Assayssupporting
confidence: 69%
“…Biodistribution analysis was performed as previously described. 23 Briefly, frozen tissues were ground to a fine powder using a pestle and mortar and processed according to manufacturer instructions (Promega, Madison, WI). Luciferase enzyme activity in supernatants was assessed using luciferase assay reagent (Promega) and normalized to total protein content.…”
Section: Neutralization Assaysmentioning
confidence: 99%
“…Note the multiple roles of the tyrosinase enzyme. different vaccination strategy and injected healthy dogs with lethally irradiated CMM cells transfected with human GM-CSF resulting in increased numbers of macrophages, which may act as APCs, at the vaccination site compared to non-transfected tumour cell vaccines (Hogge et al, 1999). In a further trial, Finocchiaro and Gilkin combined autologous/allogeneic formolised tumour cells as a vaccine injected concomitantly with lethally irradiated xenogeneic cells producing human IL-2 and human GM-CSF to treat CMM patients .…”
Section: Whole Cell Vaccinationmentioning
confidence: 99%
“…Three independent trials have examined the delivery of IL-2 or GM-CSF DNA with histoincompatible cells, 5 in combination with staphylococcal enterotoxin B, 2 or in autologous tumor vaccines. 37,38 The objective response rates for these studies were 50, 33, and 20%, respectively. The first two approaches led to median survival times that exceeded the control group or the anticipated survival based on historical data (39 and 24 weeks, respectively).…”
Section: Discussionmentioning
confidence: 86%